Penyelesaian Perkara Melalui Diversi Sebagai Upaya Perlindungan Anak Pelaku Tindak Pidana - Bambang Hartono (Law Faculty of Universitas Bandar Lampung, 2015)
Completion of juvenile criminal cases through the criminal justice system mechanism is not the best way to fix bad boy behavior, because the impact is very bad for the child, for the use discretionary authority to mendiversi cases of children in conflict with the law. The problem in this research is whether that be a consideration of the use of diversion in the child's completion of the criminal case. The method used in this study using a normative approach and empirical approach. The data used are primary and secondary data. Datathat has been processed and analyzed qualitatively. Based on the results of research and discussion note that the implementation of diversion in the settlement as a child protection child criminal simply made by police, prosecutors and judges while mendiversikan not because there is no provision expressly governing the provision of child diversion